Long live the Bigmouth Buffalo (2020-11-20) - Lackmann, Alec; University of Minnesota Duluth. Department of Biology (2020)
Department of Biology Seminar by Alec Lackmann, Post-Doctoral at University of Minnesota Duluth, Friday, November 20, 2020, at 3:00 pm on Zoom, hosted by: Dr. Mark Clark Fish have long been a major part of human cultures around the world whether it be food, sport, pets, or scientific study. In most human-fish relations, fish are exploited to human’s benefit. Apart from fisheries that target invasive species, arguably their most important characteristic is sustainability, so that future generations can reap the rewards over long time periods while the species persists. Thus, crucial information such as the exploitation rate, along with an accurate understanding of specific biological parameters such as the population size, age demographics, maturation, year-class recruitment, and natural mortality rates of harvested populations is necessary. When any of this data is lacking or wildly inaccurate, fisheries collapse. This has happened time and time again in both marine and freshwater, causing major economic, ecological, and scientific losses including extinction. All these biological parameters, except for immediate population size, are based on accurate age data. Bigmouth Buffalo (Ictiobus cyprinellus) are a freshwater fish native to North America that are natural counterparts in the fight against invasive fish such as the Asian carps, and whose young are forage for predatory gamefish. Bigmouth Buffalo have long been mistakenly believed to be a fast-paced fish. It was recently documented and validated that they instead have life history attributes that differ by an order of magnitude than what was previously assumed, beginning sexual maturity near the end of their first decade of life and able to live 112 years. Several populations across northwestern Minnesota (Hudson Bay drainage) show evidence of episodic recruitment that spans 40-80 year time intervals. During 2019-2020 we found similar evidence of episodic recruitment across a widespread region of the upper Mississippi drainage in northcentral MN with ...